2000
DOI: 10.1177/147323000002800507
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Resection of Small Rectal Carcinoid Tumours Using an Aspiration Method with a Transparent Overcap

Abstract: Rectal carcinoid tumours are often small and rarely metastatic. Endoscopic resection may, therefore, be the best treatment for small tumours. We diagnosed rectal carcinoid tumours in four women and three men (mean age 53 years; range, 43 -63) between 1994 and 1999. Tumour depth was evaluated using a high-frequency ultrasonographic probe in five of the seven patients. All tumours were resected by endoscopic mucosal resection using an aspiration method with a transparent overcap. Histologically, all tumours were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…Furthermore, the 90% histologically complete resection rate by ESD in the present study is higher than the 38% to 86% rates reported by others using various conventional endoscopic resection methods, including cap-assisted EMR and EMR with a ligation device. [12][13][14]25,26 The higher histologically complete resection rate associated with ESD is clinically significant, given the advantage of complete histological resection of rectal carcinoid tumors. First, the completeness of resection influences the type of subsequent therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the 90% histologically complete resection rate by ESD in the present study is higher than the 38% to 86% rates reported by others using various conventional endoscopic resection methods, including cap-assisted EMR and EMR with a ligation device. [12][13][14]25,26 The higher histologically complete resection rate associated with ESD is clinically significant, given the advantage of complete histological resection of rectal carcinoid tumors. First, the completeness of resection influences the type of subsequent therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed resection margin tumor involvement in 14% to 62% of EMR cases. [12][13][14] Endoscopic submucosal dissection (ESD) is a powerful new method originally developed for resection of large gastric neoplasms. 15,16 Recently, ESD has been used successfully in the resection of large colorectal neoplasms.…”
mentioning
confidence: 99%
“…Endoscopic mucosal resection is reserved for complete resection of carcinoid tumors because these tumors are sessile and develop from the deep mucosal layer toward the submucosa [9,13]. However, Stinner et al [20] reported that radical resection for rectal carcinoid should be performed only after accurate histologic study of a local resected specimen.…”
Section: Discussionmentioning
confidence: 99%
“…EMR with a cap (EMR-C) uses a transparent cap and suction to excise the submucosal layer to ensure a safe vertical margin [35][36][37]. A two-channel endoscope and a holding device with which the submucosal injected portion beneath the tumor is held and lifted are used to perform two-channel EMR [27].…”
Section: Follow-up (Median; Month)mentioning
confidence: 99%